The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/bf01844747
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cysts: Clinical and neuroradiological aspects

Abstract: Lumbar and intraneural synovial cysts are uncommon lesions, although their incidence has increased since the introduction of MRI. The authors describe the results of a study comprising 23 patients with synovial cyst (5 lumbar, 19 intraneural). Neuroradiological investigations included CT scan and MRI; however, it was not always possible to diagnose the nature of the lesion. In 18 cases the lesion was removed totally including its capsule; in the other 5 cases it was removed subtotally. Seven of the 23 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…In nerve compression due to extraneural cysts, neurological signs come later and are of lower intensity compared to intraneural lesions [1]. Another possible mechanism of neurologic deficit is anterior compartment syndrome due to extension of a ganglion from the PTFJ to the anterior leg compartment [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…In nerve compression due to extraneural cysts, neurological signs come later and are of lower intensity compared to intraneural lesions [1]. Another possible mechanism of neurologic deficit is anterior compartment syndrome due to extension of a ganglion from the PTFJ to the anterior leg compartment [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates a minor female preponderance of 53 % with an age range of 16±81 years (mean age 57 years) [1,2,5,6,7,8,9,10,11,12,13,14,15,16,17]. A review of 26 published cases showed a female predominance of 66 % [17].…”
Section: Age and Gendermentioning
confidence: 94%
“…It was not possible considering clinical features alone to distinguish these patients from those undergoing MR examinations for other low back problems. The majority of patients present with chronic low back pain with 84 % exhibiting radicular symptoms [6,11,12,15,18]. In one series of 45 cases most were considered asymptomatic at the time of diagnosis [5] which differs from the current series.…”
Section: Clinical Featuresmentioning
confidence: 96%
“…Different radiographic techniques have been used to evaluate ganglion cysts and their possible joint connections at this anatomic location (Schwimmer et al, 1985;Lee et al, 1987;Burk et al, 1988;Janzen et al, 1994;Artico et al, 1997;Kim et al, 2004;McCarthy and McNally, 2004). Ultrasound (Prevot et al, 1990;Leitjen et al, 1992;Lang et al, 1994;Dubuisson and Stevenaert, 1996;Aulisa et al, 1998) and CT (Firooznia et al, 1983;Pazzaglia, et al, 1989;Gambari et al, 1990;Antonini et al, 1991) have both been used in an attempt to characterize these cysts and their origins but have fallen short when compared to optimized MRI techniques and the superior soft-tissue contrast and high spatial resolution (Leon and Marano, 1987;Coakley et al, 1995;Kuntz et al, 1996;Uetani et al, 1998;Grant et al, 2004).…”
Section: Discussionmentioning
confidence: 99%